The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00439-013-1331-2
|View full text |Cite
|
Sign up to set email alerts
|

Where genotype is not predictive of phenotype: towards an understanding of the molecular basis of reduced penetrance in human inherited disease

Abstract: Some individuals with a particular disease-causing mutation or genotype fail to express most if not all features of the disease in question, a phenomenon that is known as ‘reduced (or incomplete) penetrance’. Reduced penetrance is not uncommon; indeed, there are many known examples of ‘disease-causing mutations’ that fail to cause disease in at least a proportion of the individuals who carry them. Reduced penetrance may therefore explain not only why genetic diseases are occasionally transmitted through unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
527
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(544 citation statements)
references
References 689 publications
11
527
0
Order By: Relevance
“…Sanger sequencing revealed these likely damaging RVs in a number of unaffected relatives (as well as confirming the results of WES), which suggests considerable incomplete penetrance. Cooper et al (2013) recently reviewed incomplete penetrance for many recognized Mendelian disorders and pointed out multiple biological mechanisms may be responsible. For disorders (such as oral clefts) that have a complex and heterogeneous etiology, incomplete penetrance should be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing revealed these likely damaging RVs in a number of unaffected relatives (as well as confirming the results of WES), which suggests considerable incomplete penetrance. Cooper et al (2013) recently reviewed incomplete penetrance for many recognized Mendelian disorders and pointed out multiple biological mechanisms may be responsible. For disorders (such as oral clefts) that have a complex and heterogeneous etiology, incomplete penetrance should be expected.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Musumeci and coworkers concluded that the most possible explanation for a low frequency of a homozygous c.32-13T>G genotype in Caucasian Pompe patients was reduced or incomplete penetrance, based on the fact that these patients were phenotypically similar to those reported for patients who were compound heterozygous for their c.32-13T>G mutation and another mutation [39]. There are multiple hypotheses for reduced penetrance and efforts are underway to better understand these observations [40]. It seems highly likely that there are many more variables contributing to late-onset disease prediction and manifestation, whereas with severe disease, the presence of two severe mutations in a single gene are most likely to be the sole driving force.…”
Section: Second-tier Molecular Testingmentioning
confidence: 99%
“…As per another, the 1000 Genomes Project, there are around 20,000-23,000 different ions in synonymous and no synonymous locales of the human genome. Despite the fact that not every one of them are practically important, 530-610 of the variations have useful effect by causing in-frame cancellations and inclusions, untimely stop codons, frame shifts, or by disturbing join locales (4). In spite of various examinations, researchers are as yet confronting a colossal test in unwinding what the succession implies and in choosing whether or not a discovered variation is pathogenic.…”
Section: Introductionmentioning
confidence: 99%